Antioxidant efficiency of lycopene on oxidative stress - induced damage in bovine spermatozoa. Issue 1 (December 2016) - Tvrdá, Eva; Kováčik, Anton; Tušimová, Eva; Paál, Dušan; Mackovich, Alica; Alimov, Jakhongir; Lukáč, Norbert
Abstract Background Lycopene (LYC) is a natural carotenoid with powerful reactive oxygen species (ROS) scavenging activities. The aim of this study was to investigate if lycopene has the ability to reverse ROS-mediated alterations to the motility, viability and intracellular antioxidant profile of bovine spermatozoa subjected to ferrous ascorbate (FeAA). Spermatozoa were washed out of fresh bovine semen, suspended in 2.9 % sodium citrate and subjected to LYC treatment (0.25, 0.5, 1 or 2 mmol/L) in the presence or absence of FeAA (150 μmol/L FeSO4 and 750 μmol/L ascorbic acid) during a 6 hin vitro culture. Spermatozoa motion characteristics were assessed using the SpermVision™ computer-aided sperm analysis (CASA) system. Cell viability was examined with the metabolic activity (MTT) assay, ROS generation was quantified via luminometry and the nitroblue-tetrazolium (NBT) test was applied to quantify the intracellular superoxide formation. Cell lysates were prepared at the end of thein vitro culture to investigate the intracellular activity of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx) as well as the concentrations of glutathione (GSH) and malondialdehyde (MDA). Results FeAA treatment led to a reduced spermatozoa motility (P  < 0.001), viability (P  < 0.001) and a decline of the antioxidant capacity of spermatozoa (P  < 0.001) but increased the ROS generation (P  < 0.001), superoxide production (P  < 0.001) and lipid peroxidation (P  < 0.001). LYC administration resulted in a preservation of the spermatozoa motion parameters (P  < 0.001), mitochondrial activity (P  < 0.001) and antioxidant characteristics (P  < 0.001 with respect to SOD;P  < 0.01 in relation to CAT;P  < 0.05 as for GPx and GSH) with a concentration range of 1 and 2 mmol/L LYC revealed to be the most effective. Conclusions Our results suggest that LYC exhibits significant ROS-scavenging and antioxidant properties which may prevent spermatozoa alterations caused by oxidative stress, and preserve the functionality of male reproductive cells.